2015
DOI: 10.1002/14651858.cd008020.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Controlled cord traction for the third stage of labour

Abstract: Analysis 1.1. Comparison 1 Controlled cord traction versus no controlled cord traction, Outcome 1 Blood loss ≥ 1000 mL......... Analysis 1.2. Comparison 1 Controlled cord traction versus no controlled cord traction, Outcome 2 Manual removal of the placenta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 22 publications
0
50
0
7
Order By: Relevance
“…Thus, the difference in the AMTSL practices of the groups may have affected the results. However, because the procedures, including cord traction and uterine massage, are considered to have little or no effect [3, 4, 6], we believe that RUPO reduced the maternal blood loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the difference in the AMTSL practices of the groups may have affected the results. However, because the procedures, including cord traction and uterine massage, are considered to have little or no effect [3, 4, 6], we believe that RUPO reduced the maternal blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Cochrane review [1] summarized the benefits and risks of AMTSL and concluded that although there is a lack of high-quality evidence, AMTSL reduced the risk of hemorrhaging > 1,000 mL at the time of birth in a population of women with a mixed risk of excessive bleeding. Regarding cord traction [24] and uterine massage [5, 6], the effects of reducing maternal blood loss have been controversial. In addition, the most common cause of PPH is uterine atony, which complicates 1 in 20 deliveries and is responsible for 80% of PPH cases [7].…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 ] In view of limited benefits, and the investment needed in training of health providers, the option of omitting routine CCT from the package of AMTSL may be considered.…”
Section: Controlled Cord Traction (Cct)mentioning
confidence: 99%
“…Future research investigating the usefulness of surfactant treatment in conjunction with other treatments for MAS infants is needed. Controlled cord traction (CCT) is one component in a group of interventions known as active management of third stage labor (AMTSL) (Hofmeyr, Mshweshwe, & Gülmezoglu, 2015). CCT is a maneuver used by skilled birth attendants to encourage placental delivery immediately following birth.…”
Section: Commentmentioning
confidence: 99%
“…In addition to CCT, AMTSL also includes the use of prophylactic uterotonic at or after birth of the infant, early cord clamping and cutting, and uterine massage following placental delivery (Hofmeyr et al, 2015). In a previous Cochrane review, AMTSL was shown to decrease the risk for severe postpartum hemorrhage (>1000 ml blood loss following vaginal delivery) among women at mixed risk of hemorrhage (average risk ratio 0.34, 95% CI [0.30, 0.83]) (Begley, Gyte, Devane, McGuire, & Weeks, 2011).…”
Section: Commentmentioning
confidence: 99%